1988
DOI: 10.2323/jgam.34.39
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory quinone profiles as tools for identifying different bacterial populations in activated sludge.

Abstract: Twelve sludges from plants treating sewage or food industrial waste and ten laboratory sludges acclimated to synthetic sewage were investigated for quinone composition. All tested sludges contained both ubiquinone and menaquinone, and some sludges also produced smaller amounts of demethylmenaquinone and/or rhodoquinone. All the sludges had Q-8 as the most predominant ubiquinone, Q-10 as the second homologue, and Q-9 and other ubiquinones as minor components. The menaquinone profiles of the sludges were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 16 publications
(37 reference statements)
7
60
0
Order By: Relevance
“…During the past decade, microbial quinones from mixed populations in activated sludge and some other wastewater environments have been analyzed successfully using HPLC techniques (6)(7)(8)(9)(10)(11)19). Previous research has shown that standard activated-sludge systems in sewage treatment plants contain both menaquinones and ubiquinones with MK/ Q molar ratios of 0.6 to 1.0 (6,8,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, microbial quinones from mixed populations in activated sludge and some other wastewater environments have been analyzed successfully using HPLC techniques (6)(7)(8)(9)(10)(11)19). Previous research has shown that standard activated-sludge systems in sewage treatment plants contain both menaquinones and ubiquinones with MK/ Q molar ratios of 0.6 to 1.0 (6,8,11).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of isoprenoid quinones as biomarkers of bacterial populations in activated sludge has, in recent years, received intensive study (6)(7)(8)(9)11,19). This biomarker approach, as well as molecular methods with rRNA-targeted oligonucleotide probes (22-24) and PCRinvolved 16S rDNA libraries (1), have proven to be useful for in situ characterization of microbial communities of activated sludge without isolating and cultivating.…”
mentioning
confidence: 99%
“…Respiratory quinone profiles of activated sludge provide valuable information on the bacterial population structure of the sludge (8,9). Thus, we assessed the predominant bacteria in sugar waste activated sludge by performing a quinone profile analysis before isolation.…”
Section: Isolationmentioning
confidence: 99%
“…Fatty acid methyl ester analysis was performed by MIDI Labs on whole cells grown on TSA incubated at 28 u C for 24±2 h according to Sasser (1997). Quinones were extracted from fresh cells of strain JA40 T by using a mixture of chloroform and methanol (2 : 1, v/v) (Hiraishi, 1988). The extracts were filtered and evaporated to near dryness.…”
mentioning
confidence: 99%